Are married women spatially constrained? A test of gender differentials in labour market outcomes - Harminder Battu; Paul Seaman; Peter Sloane (European Regional Science Association (ERSA), 1998)
Numerous studies have shown that females fare less well than males in terms of relative earnings and occupational attainment, but few acknowledge the role played by differential gender migration patterns. This paper examines the relationship between marital status, spatial migration and various aspects of female labour market outcomes. It builds on the existing literature by analysing the issue for the first time using British data and focuses particularly on the possibility of constrained migration resulting in overeducation. Our research utilises the only British dataset - the Social Change and Economic Life Initiative (SCELI) dataset - that allows the measurement of overeducation alongside other dimensions of labour market outcomes.
Keywords: 330